Status of anthelmintic resistance of gastrointestinal nematodes in organized sheep and goat farms (Asian Journal of Medical and Biological Research, 2018)
Anthelmintic resistance has become a global problem that threatens livestock production worldwide. The present study was investigated the status of anthelmintic resistance in gastrointestinal (GI) nematodes of small ruminants in two organized sheep and goat farms in two different areas of Bangladesh by fecal egg count reduction test (FECRT) for albendazole, levamisole and ivermectin. In each farms, naturally infected animals were divided into four groups of 10 animals. Fecal samples from each group were collected on day 0 and day 14 of post treatment to measure the eggs per gram of feces (EPG). The fecal samples of each group before and after treatment were also considered for culture to identify resistant parasite. In case of organized sheep farm, the result of FECRT of albendazole was 90.17, 95% confidence with upper and lower limit was 97.82 and 55.68, respectively. The result of FECRT of levamisole and ivermectin was 98.25 and 96.77, 95% confidence with upper and lower limit was 99.79, 85.12 and 99.11, 88.31, respectively. In case of organized goat farm, the result of FECRT of albendazole was 100, 95% confidence with upper and lower limit was 0 and 0, respectively. The result of FECRT of levamisole and ivermectin was 97.99 and 100, 95% confidence with upper and lower limit was 99.59, 90.28 and 0, 0 respectively. The results revealed that gastrointestinal nematodes were found to be resistant to albendazole in organized sheep farm and suspected to be resistant to levamisole and ivermectin. In organized goat farms, the GI nematodes found to be susceptible to all anthelmintics used for this study. Coproculture revealed that Haemonchus spp. were resistant parasite in sheep farm. This seems to be the first documentation of anthelmintic resistance against GI nematodes in organized sheep and goat farms in Bangladesh. Appropriate measures need to be taken to overcome the situation.Asian J. Med. Biol. Res. December 2018, 4(4): 378-382